2018
DOI: 10.1159/000488760
|View full text |Cite
|
Sign up to set email alerts
|

Trends in the Management of Nonviable Pregnancies of Unknown Location in the United States

Abstract: Background: When managing a nonviable pregnancy of unknown location (PUL), a debate has emerged in the literature whether to perform uterine curettage for definitive diagnosis of pregnancy location or administer methotrexate for a presumed ectopic pregnancy. The purpose of this study is to describe the treatment patterns when managing a PUL. Methods: A prospective, anonymous Internet based-electronic survey of PUL case scenarios was administered to a random sample of physicians across the United States. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…[1][2][3][4] There is currently no consensus regarding the optimal strategy for the management of women with a persisting pregnancy of unknown location, and management currently appears to vary among clinics and clinicians. 2,3,5 Uterine evacuation can confirm an intrauterine pregnancy loss (miscarriage) by the presence of chorionic villi on pathology. If the serum hCG concentration does not decline after uterine evacuation, the pregnancy is presumed to be extrauterine and can be treated medically with methotrexate (a competitive inhibitor of dihydrofolate reductase).…”
mentioning
confidence: 99%
“…[1][2][3][4] There is currently no consensus regarding the optimal strategy for the management of women with a persisting pregnancy of unknown location, and management currently appears to vary among clinics and clinicians. 2,3,5 Uterine evacuation can confirm an intrauterine pregnancy loss (miscarriage) by the presence of chorionic villi on pathology. If the serum hCG concentration does not decline after uterine evacuation, the pregnancy is presumed to be extrauterine and can be treated medically with methotrexate (a competitive inhibitor of dihydrofolate reductase).…”
mentioning
confidence: 99%
“…Our primary analysis will be conducted according to the principal of intention to treat to obtain an objective measure of efficacy of each management strategy. However, it is anticipated the subjects and clinicians have opinions regarding the optimal management of a PPUL [19]. We plan to collect data on why the initial management strategy may be changed.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, both early miscarriage and early ectopic pregnancy can be managed expectantly, [1317] and one multicenter randomized controlled trial demonstrated no difference in the primary treatment success of either single-dose methotrexate versus expectant management [18]. Often the strategy of choice for the management of a PPUL is based on geographic location and training [19].…”
Section: Introductionmentioning
confidence: 99%
“…Perhaps the largest confusion surrounds the management of non-viable pregnancies of unknown location (PUL), both regionally within the USA and globally. Survey data from the USA reveals that physicians are split between offering uterine curettage first versus presumptive methotrexate [17], while expectant management is frequently used in Europe for subgroups of patients [18,19]. Results from an ongoing BReproductive Medicine Network^multicenter randomized trial comparing the three management strategies will provide new data to guide clinicians in this context.…”
Section: Ectopic Pregnanciesmentioning
confidence: 99%